KAPASITAS SAMBUNGAN BALOK PRECAST SISTEM BOLT AND WET CONNECTION DENGAN OPTIMASI CAMPURAN AGREGAT DAN SIKAGROUT 215 - Andreas Rudi; Eka Sasmita (Construction and Material Journal, 2023)
The Government of Indonesia has recently made regulation about Rusun/Rusunawa in great quantities with less time for construction. The solution is using straightforward construction for Rusun/Rusunawa. The alternative to these problems is precast construction. The method of loading test is referred to ASTM C78. Having research precast beam with mixing material grouting between nonshrinkage material by Sika 215 product and coarse aggregate with ratio 50%, 40% and 30% of percentage coarse aggregate by Sika Grout 215 weight. The result achieved, (a) deflection of conventional beam K1 2,8 mm achieve at load 7,2 ton (b) deflection of conventional beam K2 2,8 mm achieve at load 8,3 ton (c)deflection of precast beam P1 2,8 mm achieve at load 2,7 ton (d)deflection of precast beam P2 2,8 mm achieve at load 3,4 ton.